2010
DOI: 10.1186/1477-7819-8-91
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided central venous catheterization in cancer patients improves the success rate of cannulation and reduces mechanical complications: A prospective observational study of 1,978 consecutive catheterizations

Abstract: BackgroundA central venous catheter (CVC) currently represents the most frequently adopted intravenous line for patients undergoing infusional chemotherapy and/or high-dose chemotherapy with hematopoietic stem-cell transplantation and parenteral nutrition.CVC insertion represents a risk for pneumothorax, nerve or arterial punctures. The aim of this prospective observational study was to explore the safety and efficacy of CVC insertion under ultrasound (US) guidance and to confirm its utility in clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
6

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 39 publications
6
58
1
6
Order By: Relevance
“…The findings of the current study showed no clinical complications of catheterization in Group 1 (SAG), while this measure was 0 -3% in other studies (1, 7-9, 11-17, 19, 21). The incidence rate of hematoma was also 0% in this study and 0 -4.3% in other investigations (1,7,8,11,13,(15)(16)(17). Moreover, there was no statistically significant difference between the two groups with respect to primary mechanical complications.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…The findings of the current study showed no clinical complications of catheterization in Group 1 (SAG), while this measure was 0 -3% in other studies (1, 7-9, 11-17, 19, 21). The incidence rate of hematoma was also 0% in this study and 0 -4.3% in other investigations (1,7,8,11,13,(15)(16)(17). Moreover, there was no statistically significant difference between the two groups with respect to primary mechanical complications.…”
Section: Discussionsupporting
confidence: 45%
“…Total success rate of catheterization was 100% in both groups, while it was reported as 93.9 -100% in other studies (1,15,16). Successful catheterization rate in the first attempt was 85% in Group 1 (SAG) compared to 63 -100% in other investigations (8,9,13,(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Onkológiai betegekben és gyermek-intenzívosztályon az ultrahangvezérelt centrálisvéna-biztosítást korrigálatlan véralvadá-si zavar mellett is biztonságosnak találták több tanulmányban is [8,9,10,11]. Felnőtt-intenzívosztályon azonban hasonló vizsgálatot még nem végeztek, a véral-vadási zavar korrekcióját szabályozó protokoll ultrahangvezérelt érkanülálások számára nem elérhető, az operatőrök gyakorlata ilyen szempontból jelentősen kü-lönbözik.…”
Section: Vje = Vena Jugularis Externaunclassified
“…Kiemelendő, hogy a véletlen artériapunkció gyakorisága ultrahangvezérléssel a tizedére, 0,5-1%-ra csökkenthető [6,7]. Az ultrahangvezérelt centrálisvéna-biztosítást több vizsgálat is biztonságosnak találta véralvadási zavar jelenlétében is, elsősorban onkológiai betegeknél, illetve egy kis esetszámú friss tanulmány gyermek-intenzívosz-tályon [8,9,10,11]. Felnőtt-intenzívosztályon viszont hasonló vizsgálat még nem történt.…”
Section: Megbeszélésunclassified